KAJIAN UPAYA PENGHEMATAN AIR BERSIH DI KANTOR DINAS PERHUBUNGAN KABUPATEN PASURUAN - Alfan Purnomo (Purifikasi, 2021)
The rapid growth of population, industry and offices has increase water consumption. One of the government’s efforts to reduce water consumption stated in the Presidential Instruction No. 13/2021 which regulates about water saving program in governmental office buildings. The Department of Transportation of Kabupaten Pasuruan does not have a water saving program yet. The purpose of this study is to identify water use and the efforts that should be taken in water saving program in the Department of Transportation of Kabupaten Pasuruan office building. This study is carried out through a field study with direct interview and observation. A water saving strategy is then planned by considering the management and technological aspects that also include financial efficiency estimation. The result of this study shows that the efficiency of water saving in stage 1 (2021 – 2022) by making management recomendations, repairing leaking pipes and faucets, for PDAM water is 20.6% and for well water is 20.69%. In stage 2 (2023 – 2024) by changing the squat toilet to a toilet flush the estimated efficiency for PDAM water is 34% and for well water is 20%. In stage 3 (2025 – 2029) by installing water meters and use of rainwater the estimated effieciency for PDAM water is 4%. Stage 4 (2030 – 2032) by recycling domestic wastewater the estimated efficiency for PDAM water is 34%. Estimated fnancial efficiency per month that can be obtained in stage 1 is Rp. 678.298, stage 2 is Rp. 246.291, stage 3 is Rp.43.149, and stage 4 is Rp 371.901.